SOCIALIZATION OF GADGET MONITORING IN CHILDREN - Wiryany, Detya; Humaedi, Muhammad Arfan; Maulana, Niko Nur; Muliawan, Riyan Candra; Aurenevia, Shafira; Sabila, Khansa (Universitas INABA, 2022)
Parent-child communication with a